2019
DOI: 10.21203/rs.2.9797/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Purtscher-like retinopathy presented a honeycomb-like pattern in optical coherence topography angiography

Abstract: Background To report a case of Purtscher-like retinopathy (PUR) and his optical coherence tomography (OCT) and OCT-angiography (OCT-A) findings before and after treatment. Case presentation A 65-year-old male presented with acute onset of vision loss for 2 weeks. Fundus examination revealed cotton-wool spots, retinal hemorrhage, and purtscher flecken spreading around the optic disc in the right eye. He was diagnosed with Purtscher-like retinopathy because of the absent reports of any traumatic medical history… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…2,[6][7][8] There are few case reports of Purtscher-like retinopathy accompanied by OCT-A images, but, to our knowledge, none in association with retrobulbar anesthesia. 4,9,10 Similar to the imaging in the study by Li et al, our OCT-A showed poor perfusion of the inner retinal vascular plexuses and a honeycomb-like hypointensity in outer retina/choriocapillaris layers. 4 These ischemic areas corresponded to the Purtscher flecken noted in the inner retina.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…2,[6][7][8] There are few case reports of Purtscher-like retinopathy accompanied by OCT-A images, but, to our knowledge, none in association with retrobulbar anesthesia. 4,9,10 Similar to the imaging in the study by Li et al, our OCT-A showed poor perfusion of the inner retinal vascular plexuses and a honeycomb-like hypointensity in outer retina/choriocapillaris layers. 4 These ischemic areas corresponded to the Purtscher flecken noted in the inner retina.…”
Section: Discussionsupporting
confidence: 87%
“…4,9,10 Similar to the imaging in the study by Li et al, our OCT-A showed poor perfusion of the inner retinal vascular plexuses and a honeycomb-like hypointensity in outer retina/choriocapillaris layers. 4 These ischemic areas corresponded to the Purtscher flecken noted in the inner retina. Li et al conjectured that this choroidal lobular infarction was the causative pathogenesis for lack of visual recovery in their patient.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations